Synergistic immune and antinociceptive effects induced from the combination of two different vaccines against morphine/heroin in mouse - Susana Barbosa-Mendez; Maura Matus-Ortega; Ricardo Hernandez-Miramontes; Alberto Salazar-Juárez (Taylor & Francis Group, 2021)
Animal studies have reported the use of different opioid-vaccine formulations with relative success These studies have suggested that new opioid-vaccine formulations are required, which are capable of triggering a robust humoral response. One strategy that has been used is the co-administration of two or more vaccines with different but complementary properties, which are capable of generating a robust immune response. We have developed two formulations of opioid-vaccine, the M6-TT, and M3-TT, which generate a robust immune response capable of recognizing heroin and morphine. In this work, we evaluate the combination of two vaccine formulations, which we call the M3/6-TT vaccine, to elicit a robust immune response and protection against heroin and morphine. Balb/c mice were immunized simultaneously with M6-TT vaccine and with M3-TT vaccine. A solid-phase antibody-capture ELISA was used for monitoring antibody titer responses after each booster dose in vaccinated animals. The study used tail-flick and hot-plate testing to evaluate the antinociceptive effects induced by heroin or morphine. Immunization with M3-TT and M6-TT vaccine elicits a robust immune response with an antibody titer of 1: 590 000 able to recognize heroin and morphine. These antibodies are capable of reducing the antinociceptive effects induced by doses of up to 40 mg/Kg. of morphine or 10 mg/kg of heroin. This suggests that the combination of two vaccine formulations that generate antibodies with different but complementary characteristics would be a new therapeutic strategy aimed at reducing drug relapses.